ANALYSIS STRATEGY MARKETING VEHICLE EDUCATION SUKAHAJI WATERBOOM - R. Hozin Abdul Fatah; Oxsa Setiawan (LKP DCI, 2023)
Study This aim For know For know how the marketing strategy is carried out Vehicle Education Sukahaji water boom . In this study the approach used by the author is descriptive qualitative, Research done in Vehicle Education Sukahaji Waterboom Kabu paten _ Nice having its address at Jl Raya Cihaurbeuti, RT.001 / RW.001 Sukahaji Village, District Cihaurbeuti, Ciamis Regency Java Province West . Retrieval technique sample in research This is purposive sampling. Method data analysis used adag SWOT analysis with matrix used _ are IFAS (Internal Strategy factors analysis Summary) and EFAS ( External Strategy factors Analysis Summary). For informants in this study, researchers grouped informants into 2 (two) groups, namely key informal, namely the top manager or general manager at the Sukahaji Waterboom Education Center, and the second, namely the main informants who have authority in deciding strategic policies at the Sukahaji Education Forum. water boom . From the results of the analysis on the IFAS table, the strengths and weaknesses have a total score of 2.34. So it indicates that the internal position of the company is very strong. Caused by a variety of products and also a strategic location and affordable prices ; opportunity and threat factors have a total score of 2.43. Because the total score is more than half of 4.0, this means that this indicates that change responds well to existing opportunities and avoids threats that come from competitors or from unforeseen circumstances (weather).